Akuntansi Aset Budaya Songkok Recca: Pengakuan dan Pengungkapan Berbasis Interaksi Simbolik Nilai Bugis - Nur Isma Arham; Nur Aipa; Septiani Wulan Purnamasari; Muhammad Yamin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Songkok Recca is a cultural heritage of the Bugis community that embodies historical, social, and symbolic values. However, its recognition and disclosure as a heritage asset have largely emphasized its physical characteristics rather than the cultural values embedded within it. This study aims to analyze the recognition and disclosure of Songkok Recca as a heritage asset through the perspective of symbolic interactionism. The study employs a qualitative interpretative approach using a documentation study method. Data were collected from scholarly journals, books, conference proceedings, and other relevant documents discussing Songkok Recca, Bugis culture, symbolic interactionism, and heritage asset accounting, and were analyzed using qualitative content analysis. The findings indicate that Songkok Recca fulfills the characteristics of a heritage asset because it embodies historical, social, and symbolic values reflected in its recca, thread, and motif elements. The disclosure of Songkok Recca should encompass its historical background, symbolic meanings, cultural philosophy, social functions, and preservation efforts to support transparency, accountability, and the sustainable management of cultural heritage assets.